Leg stiffness and expertise in men jumping - Laffaye, G.; Bardy, B. G.; Durey, A. (Medicine & Science in Sports & Exercise, 2005)
Purpose: The aim of the present study is to investigate: a) the leg spring behavior in the one-leg vertical jump, b) the contribution of impulse parameters to this behavior, and c) the effect of jumping expertise on leg stiffness.